Isoniazid Preventive Therapy and Pregnancy Outcomes in Women Living With Human Immunodeficiency Virus in the Tshepiso Cohort. (21st October 2019) - Salazar-Austin, Nicole; Cohn, Silvia; Lala, Sanjay; Waja, Ziyaad; Dooley, Kelly E; Hoffmann, Christopher J; Chaisson, Richard E; Martinson, Neil
Abstract: Background: Both pregnancy and human immunodeficiency virus (HIV) increase the risk of tuberculosis disease, which results in poor maternal, pregnancy, and infant outcomes. Isoniazid preventive therapy (IPT) reduces mortality among individuals living with HIV in high-burden settings but has recently been associated with adverse pregnancy outcomes when initiated during pregnancy. Methods: In this secondary analysis, we used multivariable logistic regression to evaluate the association between IPT exposure and adverse pregnancy outcomes (fetal demise, prematurity, low birth weight, congenital anomaly) in pregnant women living with HIV enrolled as controls in the Tshepiso study, a prospective observational cohort of pregnant women living with HIV with and without tuberculosis disease in Soweto, South Africa, from 2011–2014. Results: There were 151 women enrolled with known pregnancy outcomes; 69 (46%) reported IPT initiation during pregnancy. Of the 69 IPT-exposed women, 11 (16%) had an adverse pregnancy outcome compared with 23 (28%) IPT-unexposed women. The adjusted odds of having an adverse pregnancy outcome was 2.5 (95% confidence interval, 1.0–6.5; P = .048) times higher in IPT-unexposed women compared with IPT-exposed women after controlling for maternal age, CD4 count, viral load, antiretroviral regimen, body mass index, and anemia. Conclusions: IPT exposure during pregnancy was not negatively associated with pregnancy outcomes after controlling for demographic, clinical, and HIV-related factors. These results provide some reassurance that IPT can be safely used in the second or third trimester of pregnancy. Additional research is needed to evaluate the safety of IPT and new short-course tuberculosis preventive therapies during pregnancy. Abstract : In this secondary analysis of pregnant women living human immunodeficiency virus (HIV) with and without isoniazid exposure for tuberculosis prevention during pregnancy, we did not observe a negative association between isoniazid preventive therapy use and pregnancy outcomes after controlling for demographic, clinical, and HIV-related confounding factors.